Polystichum duyunense (subg. Haplopolystichum; Dryopteridaceae), a new cave fern from Guizhou, China - Miao, Xin-Yuan; Li, Chun-Xiang; Zhang, Li-Bing (Phytotaxa, 2017)
A new cave fern of Polystichum (subg. Haplopolystichum; Dryopteridaceae), P. duyunense, is described from a limestone cave in southern Guizhou, China. Polystichum duyunense is most similar to P. cavernicola in having oblong pinnae, but the former has pinnae larger, often angled basiscopically, and somewhat imbricate, while the latter has pinnae smaller, angled acroscopically, and apart from each other.